Off-piste Bock and Vincenzi - Jennings, Luke (Dance Books Ltd., Alton,Hampshire (UK), 2008)
Simon Vincenzi is the directorial half of the choreographic duo Bock and Vincenzi. He and Frank Bock have been collaborating since 1995.